Antimicrobial Activities of Isothiocyanates Against Campylobacter jejuni Isolates - Dufour, Virginie; Alazzam, Bachar; Thepaut, Marion; Ermel, Gwennola; Baysse, Christine (Frontiers in Cellular and Infection Microbiology, 2012)
Food-borne human infection with Campylobacter jejuni is a medical concern in both industrialized and developing countries. Efficient eradication of C. jejuni reservoirs within live animals and processed foods is limited by the development of antimicrobial resistances and by practical problems related to the use of conventional antibiotics in food processes. We have investigated the bacteriostatic and bactericidal activities of two phytochemicals, allyl-isothiocyanate (AITC) and benzyl-isothiocyanate (BITC), against 24 C. jejuni isolates from chicken feces, human infections and contaminated foods, as well as two reference strains NCTC11168 and 81-176. Both AITC and BITC displayed a potent antibacterial activity against C. jejuni. BITC showed a higher overall antibacterial effect (MIC of 2.5 to 5 g mL-1) compared to AITC (MIC of 50 to 200 g mL-1). Interestingly, the 24 C. jejuni isolates could be classified in 3 groups according to their sensitivity levels to both compounds, suggesting that AITC and BITC shared identical activity mechanisms and consequently faced similar resistance processes in bacterial cells. The sensitivity levels of C. jejuni strains against isothiocyanates were neither correlated with the presence of a GGT (-Glutamyl Transpeptidase) encoding gene in the genome nor with the origin of the biological sample. However the ggt mutant of C. jejuni 81-176 displayed a decreased survival rate compared to WT when exposed to ITC.